Examining the potential impacts of processes associated with urbanization and land use changes on inundation depths in areas affected by Hurricane Harvey in Houston. Issue 4 (8th August 2021) - Liew, Hui-Peng; Eidem, Nathan
ABSTRACT: This study explored to examine the potential impacts of population change and processes associated with urban development and land use changes on damage levels due to Hurricane Harvey in the greater Houston area. Results from linear mixed effects modeling suggested that certain social and demographic aspects of urbanization such as population growth, increase in the number of housing units, and management and professional occupations can be detrimental to the ecosystem of the greater Houston area. Another important finding was that damage-levels due to the hurricane were more severe in zip codes characterized by declines in median household income and increased unemployment. Emergency response planning and mitigation should focus on these areas.